Influenza pandemics throughout Brazilian history - Ian William Olivo Read; Aldo Musacchio (História, Ciências, Saúde: Manguinhos)
Abstract Brazil has experienced several major epidemics of influenza, and the most destructive was in 1918-1919. This article focuses on mortality, mitigation policies, and the consequences of pandemic influenza during the national period. We provide the first mortality estimates for the 1890-1894 influenza pandemic and correct figures for later epidemics. The 1918-1919 episode cost more lives than assumed, although some cities suffered less, possibly because of public health actions. Influenza caused pandemics in 1957, 1968, 1976, and 2009, but these did not cause unusual outbreaks in Brazil.